2023
DOI: 10.1002/cbdv.202300776
|View full text |Cite
|
Sign up to set email alerts
|

Petroselinum crispum Extract Prevents Scopolamine‐Induced Lens Damage in Rats

Onur Ertik,
Seren Ede Pazarbaşı,
Goksel Sener
et al.

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease that occurs especially in advanced ages. It reduces quality of life of both the patient and their relatives. In addition to its primary effects, AD causes metabolic defects and tissues are damaged due to these effects. Oxidative stress damages cells by disrupting antioxidant/oxidant balance in many tissues, especially due to AD. In individuals with AD and the elderly, lens tissue is damaged due to oxidative stress and may cause vision loss. Therefore, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…It was determined that lipid peroxidation, NO, and advanced oxidation protein products, which increased with scopolamine, decreased with the extract. As a result, it was concluded that it can reduce oxidative damage and protect lens tissue against oxidative damage due to Alzheimer's disease, owing to its rich content of phenolics and flavonoids [85].…”
Section: Neuroprotective Activitymentioning
confidence: 99%
“…It was determined that lipid peroxidation, NO, and advanced oxidation protein products, which increased with scopolamine, decreased with the extract. As a result, it was concluded that it can reduce oxidative damage and protect lens tissue against oxidative damage due to Alzheimer's disease, owing to its rich content of phenolics and flavonoids [85].…”
Section: Neuroprotective Activitymentioning
confidence: 99%